The Implementation of Educational Debating Method to Foster Students' Speaking Ability - Nunung Nurjannah; Umarah Muhadharah (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
The research aims to investigate how the educational debating method can foster the students' speaking ability at the eleventh grade of SMAN 1 Sumber and to find out how the students' activities in learning speaking using the educational debating method in fostering students' speaking ability. This research primarily used a quantitative method to analyze the data with quasi-experimental method was chosen to test the hypothesis because the study focused on only one aspect of investigating, namely speaking ability withiut controlling all variables. There were two classes consisting of 28 students each class as sample in SMAN 1 Sumber. The data was obtained by analyzing students' speaking scores, observation sheet, and questionnaire results. The research found that the speaking scores of the experimental group was higher than the control group and it was also supported by the students' activities from the questionnaire. The students felt that educational debating method can foster their speaking. It made the students enthusiastic to learn and help them to understand the matter of the subject. It was a pleasant and good method in teaching spaking, especially for asking and giving opinion. The students liked to participate in the use of educational debating method because they had an opportunity to study in pairs and improved their achievement in speaking by knowing pronunciation, vocabulary, and grammar.